I'm trying to find a closed form for the sum: $$\sum_{n=2}^\infty \frac{\ln(n)(-1)^n}{n^2} $$

It's been proven, $$\sum_{n=2}^\infty \frac{\ln(n)(-1)^n}{n} = \gamma\ln(2)-\frac{\ln(2)^2}{2}$$

Since they're similar, I feel there potentially could be a closed form solution of the first one. I want to know if there is also a closed form solution for the first summation.

I managed to rewrite the first sum as a double integral:

$$-\int_0^1\int_0^1 \frac{\ln(x)}{\ln(y)}\left(\frac{1}{1+x}-\frac{1}{1+xy} \right)dxdy $$ But I don't see any overt way of evaluating it. I've tried differentiating under the integral, but to no avail. I can't think of any change of variables that would help simplify as well.

  • 5
    $\begingroup$ Well, $\sum_{n=2}^\infty \frac{\ln(n)(-1)^n}{n} $ is the derivative of eta funtion in $1$, see here: en.wikipedia.org/wiki/Dirichlet_eta_function#Derivatives. Why not plug $s=2$? $\endgroup$ – Zacky Jan 4 '19 at 15:22
  • $\begingroup$ I see thank you $\endgroup$ – Tom Himler Jan 4 '19 at 15:26
  • 3
    $\begingroup$ You're welcome, but there is still some work to do. From here:en.wikipedia.org/wiki/Glaisher%E2%80%93Kinkelin_constant we can find a value for $\zeta'(2)$ and we should arrive at: $$\sum_{n=2}^\infty \frac{\ln(n)(-1)^n}{n}=\eta'(2)=\frac{\pi^2}{12}\left(\ln(4\pi) -12\ln(A) +\gamma\right)$$ $\endgroup$ – Zacky Jan 4 '19 at 15:34
  • 1
    $\begingroup$ Just so you know, in your sum I think you forgot to square the denominator. Right now, the sum reads $\eta'(1)$. $\endgroup$ – Zachary Jan 4 '19 at 16:41
  • $\begingroup$ From differentiating $\eta(s)=(1-2^{1-s})\zeta(s)$, we obtain $\eta'(s)=\zeta(s)2^{1-s}\log 2+\big(1-2^{1-s}\big)\zeta'(s)$. However, I am not sure what happens near $s=1$, as the left side should be well defined, but the right side does not seem to be. $\endgroup$ – Zachary Jan 4 '19 at 22:35

The definition of $\eta(s)$ is $$\eta(s)=(1-2^{1-s})\zeta(s)$$ Take the derivative, and we get by product rule $$\eta'(s)=2^{1-s}\ln(2)\zeta(s)+(1-2^{1-s})\zeta'(s)$$ $\eta(s)$ also has the following series representation $$\eta(s)=\sum_{n=1}^{\infty}\frac{(-1)^{n-1}}{n^s}$$ Again, take the derivative $$\eta'(s)=\sum_{n=2}^{\infty}\frac{(-1)^{n}\ln(n)}{n^s}$$ Now, we can obtain a closed form $$\eta'(2)=\sum_{n=2}^{\infty}\frac{(-1)^{n}\ln(n)}{n^2}=2^{1-2}\ln(2)\zeta(2)+(1-2^{1-2})\zeta'(2)$$ Note that


$$\begin{align} \sum_{n=2}^{\infty}\frac{(-1)^{n}\ln(n)}{n^2}&=2^{-1}\ln(2)\zeta(2)+(1-2^{-1})\zeta'(2)\\ &=\frac{\pi^2}{12}\ln(2)+\frac{\pi^2}{12}(-12\ln(A)+\ln(2\pi)+\gamma)\\ &=\frac{\pi^2}{12}(\ln(4\pi)-12\ln(A)+\gamma) \end{align}$$

  • $\begingroup$ very nice job indeed! $\endgroup$ – G Cab May 23 '19 at 22:14
  • 3
    $\begingroup$ ($A$ is really defined as $e^{1/12-\zeta'(1)}$ appearing as the natural regularization of $\prod_{n=1}^\infty n^n$) $\endgroup$ – reuns May 23 '19 at 22:34

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.